TANGGUNG JAWAB SECARA PERDATA ATAS SERTIPIKAT TANAH YANG DISIMPAN OLEH NOTARIS/PPAT (STUDI PUTUSAN PENGADILAN NEGERI JAKARTA BARAT NOMOR: 466/PDT.G/2017/PN.JKT.BRT) - Kellie Angiarti; Endang Pandamdari (Jurnal Hukum Adigama, 2019)
Making an authentic deed is very necessary especially in the transfer of land rights. For the sake of achieving legal certainty for the community, an authorized official is required to make all authentic deeds related to the process of transfer of rights due to the sale and purchase of land, namely the Land Deed Making Official (PPAT). in practice, PPAT also serves as a notary public. The position of a PPAT as a functionary in the community is very important, because the PPAT Deed (authentic deed) as a document regarding the sale and purchase of land is proof of sale and purchase that needs to be registered at the Land Office for the issuance of the Land Rights Certificate. Notary / PPAT must work responsibly, independently, honestly, and protect the interests of related parties in legal actions. This shows that Notary / PPAT is a profession that is required in fulfilling moral values and its development. But in reality, not all Notaries / PPAT carry out their obligations properly, for example, can be seen in the Decision of the West Jakarta District Court Number: 466 / Pdt.G / 2017 / PN.Jkt.Brt where the event of the loss of Land Rights Certificate which is kept by the Notary Public in his position as the Land Deed.